Efektivitas dan Ef"lSiensi SMS Gateway Menggunakan Multi Modem - Leong, Hironimus; Cristianti, Risa Farid (PROXIES, 2013)
One goal of clustering data mining is to find a cluster of a particular data modeling. By modeling the data, it can provide more description of the data being analyzed and can be visualized in graphical form. One of the methods used in data mining to search for data modeling is to use KMeans algorithm analysis. K-Means algorithm Is used to find groupings of data with specific points, caUed the centroid. By grouping the data, then large amounts of data, grouped in a simpler visualization. The final results can be used as Decision Support System. Keyword: SMS Gateway, Multi Modem